Recognition, Measurement, Presentation and Disclosure of Corporate Social Responsibility (CSR) Costs PT. Kawasan Industri Makassar (Persero) - Widyantono Arif; Asri Usman; Adil Setiawan (Syntax Corporation Indonesia, 2022)
The study aims to determine and analyze the application of corporate social responsibility accounting at PT Kawasan Industri Makassar (Persero). This research is qualitative with a descriptive analysis approach. The results of the study indicate accounting practices (recognition, measurement, presentation, and disclosure) of the costs of corporate social responsibility by PT Kawasan Industri Makassar (Persero) are under the Basic Framework for the Preparation and Presentation of Financial Statements (KDPPLK). PT Kawasan Industri Makassar (Persero) already has a specific financial report that refers to SAK ETAP, which is oriented to the non-profit sector by establishing a Small Business and Cooperative Development Unit, which is now called the Partnership and Community Development Program Unit (PKBL) which has been edited by Public accounting firm. There are no normative rules related to the cost accounting for CSR and the importance of environmental and social factors, so the findings of this study have practical implications for other business actors who should have their own business units that focus on social and environmental aspects.